Argon plasma coagulation offers survival benefit compared with stent placement in the palliative treatment of inoperable oesophageal cancer; a retrospective single centre experience. (13th March 2011) - Krystallis, C; Paterson-Brown, S; Plevris, J N
Abstract : Introduction: Over 2/3 of patients diagnosed with oesophageal cancer (Ca) are not surgical candidates and require palliative treatment. Endoscopic therapy with self expanding metal stents (SEMS) or thermal ablative techniques (laser, APC) are commonly used for palliation. Although SEMS have no direct effect on tumour growth, they improve clinical condition by improving nutritional status, and by preventing dehydration and aspiration. A randomised trial comparing laser with metal stent for palliation of oesophageal Ca, demonstrated significantly longer survival in the thermal tumour ablation group a few years ago. APC is considered an effective palliative treatment for debulking exophytic oesophageal tumours, and is associated with clinical improvement of tumour-related symptoms including dysphagia and anaemia. However it is not known whether APC is associated with improved survival compared with SEMS, in patients who are not candidates for surgery or chemo-radiotherapy (CRT). The study aim was to compare survival of patients with inoperable Ca of the oesophagus who received APC versus SEMS as primary treatment. Methods: Retrospective study of 209 patients retrieved from endoscopy database with inoperable ca of the oesophagus/oesophago-gastric junction extending to the oesophagus, who received palliative treatment with APC (Group A) or SEMS (Group B) over a 10-year period. We excluded 56 patients received CRT before or after APC/stent placement. All cases were discussed at local multidisciplinary meeting and details about co-morbidity (Charlson co-morbidity index) and tumour staging were available in all patients studied. Kaplan-Meir survival curves and log-rank median survival comparisons were carried out between the two groups matched by disease stage. Results: From a total of 153 patients, APC (on intention to treat) was given to 61 (Group A) and stents to 92 patients (Group B) respectively. Mean age and gender (M/F) (76.55, 42/19 vs 76.28, 59/33) in group A and B respectively. The comparisons of median survivals between groups overall and subgroups of same disease stage are: Group A versus B overall 275 days ± 22.3 versus 112 ±17.58 (log rank p<0.0001), stage III-IV disease 241 days±24.5 versus 110±15.9 (log rank p<0.0001), stage III disease 300 days±28.62 versus 147±6.08 (log rank p<0.0001). All groups in comparison had no differences in comorbidity. Conclusion: This the first evidence that APC prolongs survival in patients not candidates for surgery or CRT compared with stenting. Stenting should be reserved for cases that APC can no longer maintain lumen patency. Further prospective evaluation is worthy.